2017
DOI: 10.12687/phleb2373-3-2017
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of varicose veins

Abstract: SummaryBackground: In the search of alternative techniques to high ligation and stripping (HL/S) in the treatment of varicose veins, catheter-ablation methods have been implemented since 1998. Besides endovenous laser techniques (ELT) radiofrequency ablation (RFA) is a successful device in treating insufficiency of the Great (GSV) and Small saphenous vein (SSV). Methods: This review article sums up publications on Closure Plus™, ClosureFAST™, RFITT® (Celon Method), and EVRF®. It discusses the actually favorize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
2
Order By: Relevance
“…Technology advances and technical standardization have drastically reduced ACs (15). Dermody et al reported RFA complications in randomized controlled trials (RCTs), describing a decrease in bruising, haematoma and SVT in RCTs if the second-generation ClosureFast™ catheter was used, compared to cases performed with a first generation catheter ClosurePlus™ (5).…”
Section: Discussionmentioning
confidence: 99%
“…Technology advances and technical standardization have drastically reduced ACs (15). Dermody et al reported RFA complications in randomized controlled trials (RCTs), describing a decrease in bruising, haematoma and SVT in RCTs if the second-generation ClosureFast™ catheter was used, compared to cases performed with a first generation catheter ClosurePlus™ (5).…”
Section: Discussionmentioning
confidence: 99%
“…Дана методика прийшла на зміну традиційній кросектомії та видаленню недостатніх сегментів вен великої і малої підшкірних вен. Ця операція забезпечує хороший косметичний ефект, менший ризик ускладнень, оскільки все виконується з використанням місцевої анестезії та під контролем ультразвуку [2,3,9].…”
Section: загальна хірургія (всі хірургічні дисципліни)unclassified
“…Radyofrekans ablasyon tedavisi de (RFA) bu yöntemlerdendir. Endovenöz ablasyon tedavilerinden ilk olarak RFA kullanılmaya başlanmış ve 1999'da minimal invaziv prosedür olarak ABD Gıda ve İlaç İdaresi (FDA) tarafından onaylanmıştır (2). RFA'nın kateter maliyetinin yüksek olması, pacemakerlı hastalara uygulanamaması, radyofrekansın lazere göre derine penetrasyonunun daha fazla olması sebebiyle ısı ilişkili komplikasyonlara daha fazla neden olması gibi bazı dezavantajlarından dolayı EVLA kullanımı giderek artış göstermektedir.…”
Section: Introductionunclassified